Pemetaan Potensi Lahan Pertanian Pangan Berkelanjutan Guna Mendukung Ketahanan Pangan - Slamet Muryono; Westi Utami (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Klaten Regency is one of the potential food barns in Central Java, but its existence is increasingly threatened because the conversion of agricultural land continues to increase. This study aims to map the potential of sustainable food agricultural reserves (LCP2B) to support the spatial data presentation for the determination of Sustainable food agricultural land (LP2B). The research was conducted through spatial analysis by overlaying the existing land use data with Spatial Planning Map. The results of the study showed that in Klaten District there was 30,703 Ha. or 46.84% of the potential land for LP2B and the potential land for LCP2B location is 6,877 Ha or 10.49% so that the potential area of LP2B and LCP2B is 37,580 Ha or 57.33% of the total area of Klaten Regency. Overlay results show that the LP2B Potential Location is appropriate with the RTRW which is 25,413 Ha or 38.77% and the inappropriate is 40,143 Ha or 61.23% of the total area of Klaten Regency. The efforts to protect LP2B in Klaten Regency need to be immediately encouraged through the establishment of Regional Regulations accompanied by complete and accurate spatial data so that the sustainability of increasingly urged food agriculture lands can be realized. Determination of LP2B to prevent the conversion of agricultural land is expected to be able to realize food security and support the sustainability of the livelihoods of most people who work as farmers.Keywords: Food Security, LP2B, LCP2B Potential Map, Land Use.Intisari: Kabupaten Klaten merupakan salah satu lumbung pangan potensial di Jawa Tengah, namun keberadaanya semakin terancam karena konversi lahan pertanian terus meningkat. Kajian ini bertujuan memetakan potensi Lahan Cadangan Pertanian Pangan Berkelanjutan (LCP2B) guna mendukung tersajinya data spasial untuk penentuan Lahan Pertanian Pangan Berkelanjutan (LP2B). Penelitian dilakukan melalui analisis spasial dengan melakukan overlay data penggunaan tanah dengan peta RTRW. Hasil kajian menunjukkan di Kabupaten Klaten terdapat 30.703. Ha atau 46,84 % potensi lahan untuk LP2B, dan potensi lahan untuk lokasi LCP2B seluas 6.877 Ha atau 10,49 %, sehingga luas Potensi LP2B dan LCP2B adalah 37.580 Ha atau 57,33 % dari total luas wilayah Kabupaten Klaten. Hasil overlay menunjukkan bahwa terdapat kesesuaian antara Potensi Lokasi LP2B terhadap RTRW yakni seluas 25.413 Ha atau 38,77 % dan ketidaksesuaian seluas 40.143 Ha atau 61,23 % dari total luas wilayah Kabupaten Klaten. Upaya perlindungan LP2B di Kabupaten Klaten perlu segera didorong melalui penetapan Peraturan Daerah disertai dengan data spasial yang lengkap dan akurat sehingga keberlanjutan lahan pertanian pangan dapat terwujudkan. Penetapan LP2B dengan maksud mencegah terjadinya konversi lahan pertanian diharapkan mampu mewujudkan ketahanan pangan serta mendukung keberlanjutan penghidupan sebagian besar masyarakat yang menggantungkan hidup pada sektor agraris. Kata Kunci: Ketahanan Pangan, LP2B, Peta Potensi LCP2B, Penggunaan Tanah.